1988
DOI: 10.2320/matertrans1960.29.183
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Resistivity of Nickel, Cobalt and Their Alloys

Abstract: The electrical resistivity of nickel, cobalt and their alloys has been measured in the temperature range from 4.2 to 1600K. By using the s-d exchange-interaction constant and the numbers of conduction electrons and hole-carriers estimated in this study, the correlation between the magnetic resistivity and the ferromagnetism is discussed from the viewpoint of the scattering process due to the spin disorder containing not only the intraband s-s transition but also the interband s-d transition. It is pointed out … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1989
1989
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…In recent years, the low-temperature sintering bonding of Ag [13][14][15] and Cu [16,17] nanoparticles has been investigated and developed. However, some factors have limited the further application of Ag and Cu nanoparticles sintering, such as the low ion migration resistance of Ag [18,19] Previous studies have demonstrated that Ni nanoparticles smaller than 100 nm can function as a bonding material that can be sintered below 400°C and can exhibit higher long-term resistance to temperatures higher than 250°C. [20][21][22] A previous study reported that Ni nanoparticles can directly bond with Al in the atmosphere, even though Al does bond easily in soldering without flux processing.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the low-temperature sintering bonding of Ag [13][14][15] and Cu [16,17] nanoparticles has been investigated and developed. However, some factors have limited the further application of Ag and Cu nanoparticles sintering, such as the low ion migration resistance of Ag [18,19] Previous studies have demonstrated that Ni nanoparticles smaller than 100 nm can function as a bonding material that can be sintered below 400°C and can exhibit higher long-term resistance to temperatures higher than 250°C. [20][21][22] A previous study reported that Ni nanoparticles can directly bond with Al in the atmosphere, even though Al does bond easily in soldering without flux processing.…”
Section: Introductionmentioning
confidence: 99%